2019
DOI: 10.5812/hepatmon.85775
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Aflatoxin B1-Related TP53 Mutation Detected by Digital PCR in Tunisian Patients with and Without Hepatocellular Carcinoma

Abstract: Background: In the recent years, hepatocellular carcinoma (HCC) has become one of the first causes of cancer mortality in humans. Among the issues explaining this appalling situation the lack of early biomarkers occupies a prominent position. In patients with tumors, free circulating DNA originating from tumor cells represents a promising material for the early detection of the disease. In HCC, two mutations, R249S on TP53 and-124C>T in TERT promoter, are potentially present in large subsets of patients and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
4
0
1
Order By: Relevance
“…During our study, we noticed genetic deviations such as mutations in TP53 ( Marchio et al, 2019 ; Lleonart et al, 2005 ; Marchio et al, 2018 ), CTNNB1 ( MacDonald, Tamai & He, 2009 ), and TERT ( Yang et al, 2011 ; Akuta et al, 2021 ), which have been widely studied in circulating tumor DNA in HCC patients. However, a recent study identified TTN, TMEM141, UBB, and ADGRV1 also as the most frequently mutated genes in HCC patients, making them worthy of further investigation ( Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…During our study, we noticed genetic deviations such as mutations in TP53 ( Marchio et al, 2019 ; Lleonart et al, 2005 ; Marchio et al, 2018 ), CTNNB1 ( MacDonald, Tamai & He, 2009 ), and TERT ( Yang et al, 2011 ; Akuta et al, 2021 ), which have been widely studied in circulating tumor DNA in HCC patients. However, a recent study identified TTN, TMEM141, UBB, and ADGRV1 also as the most frequently mutated genes in HCC patients, making them worthy of further investigation ( Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
“…1 ). Eventually, the full text of 59 eligible articles (60 studies) was incorporated into this meta-analysis ( Huang et al, 2003 ; Wang et al, 2021 ; Wong et al, 2000 ; Wong et al, 2003 ; Chu et al, 2004 ; Lin et al, 2005 ; Yeo et al, 2005 ; Iizuka et al, 2006 ; Ren et al, 2006 ; Wang et al, 2006 ; Zhang et al, 2007 ; Chan et al, 2008 ; Chang et al, 2008 ; Igetei et al, 2008 ; Ahmed et al, 2010 ; El-Shazly et al, 2010 ; Hu et al, 2010 ; Huang et al, 2011 ; Iizuka et al, 2011 ; Yang et al, 2011 ; Chen et al, 2012 ; Huang et al, 2012 ; Mohamed et al, 2012 ; Chen et al, 2013 ; Sun et al, 2013 ; Zhang et al, 2013 ; Han et al, 2014 ; Huang et al, 2014 ; Ji et al, 2014 ; Kuo et al, 2014 ; Li et al, 2014 ; Yang et al, 2014 ; Dong et al, 2015 ; Huang et al, 2015 ; Ramadan et al, 2015 ; Teng et al, 2016 ; Dong et al, 2017 ; Hu et al, 2017 ; Mansour et al, 2017 ; Tian et al, 2017 ; Wu et al, 2017 ; Gai et al, 2018 ; Li et al, 2018 ; Oussalah et al, 2018 ; Wei et al, 2018 ; Linlin et al, 2018 ; Bai et al, 2019 ; Kisiel et al, 2019 ; Marchio et al, 2019 ; Pasha, Mohamed & Radwan, 2019 ; El-Bendary et al, 2020 ; He et al, 2020 ; Kotoh et al, 2020 ; Li et al, 2020a …”
Section: Resultsunclassified
See 3 more Smart Citations